Inhalant allergens in Portugal - Camacho, Irene Gomes Câmara (2021)
This review aims to present in a simple manner the work performed in Portugal regarding the identification of the most prevalent aeroallergens in the country and the sensitization levels in Portuguese patients. Much of the data was summarized in tables and illustrated on maps, enabling the community of clinicians, researchers, and patient organizations to access the knowledge about the research performed. This study provides an overview about the distribution of aeroallergens in Portugal, signaling regions and critical periods of exposure of the sensitized population. The illustrated data can help the community of allergy specialists to view the temporal and spatial distribution of aeroallergens across the country. In addition, this information can guide clinicians to select the most appropriate allergens for allergy diagnostic testing, treatment, and allergen avoidance.